Analysis of the Expression and Prognostic Value of Annexin Family Proteins in Bladder Cancer - Wu, WenBo; Jia, GaoZhen; Chen, Lei; Liu, HaiTao; Xia, ShuJie (Frontiers in Genetics, 2021)
Background Bladder cancer (BC) is the most common tumor of the urinary system. Non-muscle-invasive bladder cancer (NMIBC) has a high recurrence rate after surgery, and patients with muscle-invasive bladder cancer (MIBC) have poor quality of life after radical surgery. Understanding the molecular mechanism of bladder cancer is helpful for providing a more appropriate treatment approach. Annexins are calcium-binding proteins and play an important role in different tumor cells. However, the role of the annexin family in bladder cancer has not been studied in detail. Methods ONCOMINE, UALCAN, TIMER2.0, Kaplan-Meier Plotter, cBioPortal, and WebGestalt were utilized in this study. Results ANXA2, ANXA3, ANXA4, ANXA8, and ANXA9 were significantly increased in bladder tumor tissues, while ANXA6, ANXA7, and ANXA11 were significantly decreased. ANXA1, ANXA2, ANXA3, ANXA5, ANXA6, ANXA7, and ANXA9 had prognostic value in bladder cancer. In addition, specific annexins were specifically expressed in different subtypes of MIBC and were related to the histological morphology of bladder tumors. ANXA1, ANXA2, ANXA3, ANXA5, ANXA6, ANXA7, and ANXA8 were highly expressed in basal-subtype MIBC, while ANXA4, ANXA9, ANXA10, and ANXA11 were mainly expressed in luminal-subtype MIBC. Finally, we analyzed the possible mechanisms of ANXAs in different subtypes of bladder cancer through GO and KEGG analyses and the correlation between ANXAs and immune infiltration in the tumor microenvironment. Conclusion Taken together, our results indicate that annexins might play important roles in BC and have the potential to be used as markers for subtype classification.